Nanosized phases with titanium(IV) oxides. Preparation. Characterisation. Properties - G. M. Kuzmicheva (Тонкие химические технологии)
The solid state of samples (crystal, paracrystal, nanocrystal, amorphous), the main features of nanoobjects, their dimensional hierarchy and peculiarities of properties are considered. The main methods of studying the сomposition, substructure and microstructure characteristics of nanosized compounds are proved. The basic method is X-ray study with specific effects on a diffraction picture. By the example of samples with anatase and η-phase structures obtained by the sulfate method the results of a complex of techniques (wide-angle and small-angle X-ray diffraction, synchrotron radiation, low temperature absorption of nitrogen, IR-spectroscopy, Raman spectroscopy) for the determination of the composition and structure of nanoparticles and their functional characteristics are shown. A relationship of some characteristics and preparation conditions of samples with parameters of the adsorption and photocatalytic properties is found.